Avaliação de critérios de sucesso em um programa multiprofissional de tratamento da obesidade em adolescentes : análise em curto e longo prazo - Antonini, Vanessa Drieli Seron (2014)
Evaluate criteria of success in a multidisciplinary program of obesity treatment: analysis in short- and long-term. It was included 22 adolescents with excesso body weight aged between 10 and 18 years. It was realized anthropometric assessments, body composition, physical fitness, resting herat rate, and metabolic parameters. It was assessed pubertal development and stage of readiness to change eating and exercise behavior using the questionnaire ¨Stage of Change¨ (SOC), besides, it was assessed health-related quality of life using the generic questionnaire PedsQLTM 4.0. It was assessed after the 16-week intervention the success rate attained according to the criteria/cut off points proposed by Nardo Junior et al. following four possibilities of determination of success in separated groups (success vs not success). The rate of success was associated with sex, chronological and biological age and stage of readiness to change eating and exercise behavior. The association was verified by 2x2 Chi-square and Chi-square of tendency. After that, it was compared the results after three semesters of intervention for adolescentes who obtained and those who did not obtained success after 16 weeks of intervention. It was used the Analysis of Variance (ANOVA) for repeated measures and mixed ANOVA for repeated measures for the comparisons between moments. When diferences in baseline were observed, this moment was used as covariate and the behavioral factors associated with success in 16 weeks of intervention observed in study 1 were also used as covariates. Significance was set at p<0.05. It was also applied the analysis of magnitude of changes. Three semesters of intervention were capable to promote improvements in BMI, BMI Z score, flexibility, abdominal strength/resistance, handgrip strength, cardiorespiratory fitness, absolute and relative body fat, WC, DBP, LDL-c, HDL-c, VLDL-c, TG, RFMS and physical domain of HRQoL, besides, the criteria EsSu-ACCO and EsSu-GORD were associated with greater stages of readiness to change behaviors related to the amount of fat on diet, consumption of fruits and vegetables, increase in physical activity and the combination of all domains of SOC questionnaire (p<0.05). With respect to the success attained when the EsSu-PMTO was considered, no associations were observed, however, sex and chronological age presented associations close to significance (p <0.10) with this criterion. Independently of of the criteria used, the group who obtained success presented improvements in more parameters than the group who did not obtain success. The parameters that improved more in the success group compared to the non-success group were the risk factors for metabolic syndrome, and the analysis in magnitudes of changes confirmed that, considering that the non-success group presented more 'unclear' results. The present study observed that three semesters of multidisciplinar intervention were benefical and promoted changes in body composition, physical fitness, metabolic parameters and HRQoL, moreover, attain the success in 16 weeks of intervention may be na indicative of better results in long term. The success obtained in the criteria EsSu-ACCO and EsSu-GORD were associated with greater stages of change. No association was observed for the criterionEsSu-PMTO.